Knockdown of TOP2A reverses cisplatin resistance in ovarian cancer by inhibiting EMT via ferroptosis mediated by the TP53/GPX4/SLC7A11 axis - Liu, Xinyue; Wang, Junxia; Liu, Yangyu; Han, Yan; Qin, Zhichao; Wang, Yu; Gao, Shanxiang; Li, Xinghua; Suo, Yuping (Frontiers in Immunology, 2025)
IntroductionCisplatin resistance is a major challenge in ovarian cancer therapy, particularly for high-grade serous ovarian cancer (HGSOC). DNA topoisomerase IIα (TOP2A) relates to cancer drug resistance, yet its role and molecular mechanisms in ovarian cancer cisplatin resistance remain unclear.MethodsTOP2A expression was detected in HGSOC tissues and cisplatin-resistant cells (SKOV3-DDP, OVCAR3-DDP). Functional assays combined with TOP2A knockdown evaluated cisplatin sensitivity and malignant phenotypes (proliferation, invasion, migration) in resistant cells. RNA-seq and GEO cisplatin resistance dataset (GSE214302) validated TOP2A’s role in cisplatin resistance, prognostic value, and associations with TP53, GPX4, SLC7A11. Molecular docking/Co-IP confirmed TOP2A-TP53 interaction. Fer-1 and TP53 knockdown clarified TP53/GPX4/SLC7A11 axis regulation of ferroptosis and EMT, and an in vivo xenograft tumor model validated these findings.ResultsTOP2A is highly expressed in HGSOC tissues and cisplatin-resistant cells, with high levels strongly associated with tumor progression (advanced stage, high grade, lymph node metastasis) and poor prognosis. RNA-seq shows TOP2A correlates with TP53, GPX4, SLC7A11.GEO dataset analysis confirms all four associate with cisplatin resistance. SLC7A11 and TOP2A are effective resistance biomarkers, and high TOP2A predicts shorter progression-free survival. Molecular assays verify direct TOP2A-TP53 interaction. Functional experiments reveal TOP2A knockdown enhances cisplatin sensitivity, inhibits malignancy, activates ferroptosis, and suppresses EMT via the TP53/GPX4/SLC7A11 axis. This effect is reversed by Fer-1 or TP53 knockdown, with mechanisms validated in vivo.ConclusionTOP2A represents a potential prognostic biomarker and therapeutic target for cisplatin resistance in ovarian cancer (OC), as it regulates ferroptosis and EMT via the TP53/GPX4/SLC7A11 axis, which is mediated by its direct interaction with TP53. This thus provides a novel direction for treating cisplatin-resistant OC.